Uji Aktivitas Antioksidan Infusa Daun Alpukat (Persea americana Miller) dengan Metode DPPH - Maslena Siregar (Program Studi S1 Farmasi, STIKES Senior, Medan, 2018)
Avocado leaves (Persea americana Miller) have secondary metabolites such as polyphenols, flavonoids, saponins, tannins. Flavonoid compounds function as antioxidants to the human body. The aim of the study was to determine the antioxidant activity of avocado leaf infusion with extract concentrations of 0 ppm, 250 ppm, 500 ppm, 1000 ppm, 1500 ppm, and Vitamin C with concentrations of 0 ppm, 2.5 ppm, 5 ppm, 10 ppm, and 15 ppm. by the DPPH (1,1-Diphenyl-2-Picrihydrazil) method. The results showed that avocado leaf infusion had very weak antioxidant activity with IC50 value = 1,511.15 ppm, while the measurement results of Vitamin C had very strong antioxidant activity with IC50 value = 9,264 ppm.